Cross-school 'close-to-practice' action research, system leadership and local civic partnership re-engineering an inner-city learning community (UCL Press, 2020)
This article presents two sequential case reports of how 60 schools in the London Borough of Camden used action research in three phases of development of their local school system reform, from a traditional council-led, top-down model of centrally based professional development and monitoring of schools, to one that is schools-led and 'bottom-up' in nature, but still in close partnership with its local council and community. The article uses a sociocultural lens through which to view this journey of self-reform, tracking change through three evolutions of the sociocultural model as professional learning becomes situated in classrooms and between schools in Camden, as motivations to develop and change become increasingly intrinsic and less driven by fear of failure or the consequences of failure. Of critical importance is the feedback-rich context created by adoption of enquiry- and coaching-based learning models at classroom, organizational and system levels. This both fuels and is fuelled by the strategic collaboration of head teachers and by system leadership also provided by middle leaders, whose increased cross-school agency builds improvement capacity and collaborative capital. The article does not report on the action research alone: unlike many accounts of action research for change, this account provides a narrative backdrop in which to locate both scientific and system developments. This is provided through three short vignettes that place the changes reported in a societal, political and community context, without whose energetic actors (in the form of local political and community leaders and school governors) the local 'civic governance' so strongly behind these reforms, would not have existed.